Formulation and Characterization of Ferrous Sulphate and Lycopene Floating Matrix Tablets - R. Pradhap; Dr.C. Rubina Reichal; P. Saminathan; M. Shobana (International Journal of Pharma and Bio Sciences, 2023)
Ferrous sulphate has poor bioavailability in the upper Gastrointestinal tract and low solubility in an acidic medium. To prolong the dosage form in the stomach and increase the residence time, the drug is used as a new drug delivery system as a matrix tablet of a Floating drug delivery system. The Floating Drug Delivery System(FDDS) has many more advantages for increasing drug absorption and enhancing bioavailability. Iron is a necessary element of our body. The marketed products have less or incomplete absorption because of increased excretion of drugs or bowel transport in GIT such as constipation, black stools and diarrhoea. In this research work, ascorbic acid added to the formulation can increase iron absorption. Lycopene is an antioxidant as a supplement with ferrous sulphate. Ten formulations were formulated with different retarding polymers by direct compression method. Citric acid and Sodium bicarbonate were producing effervescent. Pre-compression and post-compression evaluation tests were done for all the designed tablets. From the in vitro release, formulation 5 (F5) showed the highest release percentage at 24 hours. The optimized formulation 5 (F5) was subjected to various release kinetics, and formulation 5 (F5) was found to obey zero order kinetics more over the peppas model was 0.45